Delta Lactate (Three-hour Lactate Minus Initial Lactate) Prediction of In-hospital Death in Sepsis Patients - Webb, Amanda L (Cureus, 2020)
This study examines the relationship between serial serum lactate levels and in-hospital mortality in an adult cohort of emergency department patients with severe sepsis or septic shock. Of the 164 patients in the cohort, 130 also got three-hour lactate in addition to the initial one. The median initial lactate was 3.01 (interquartile range [IQR]: 1.71-4.62). The median repeat lactate was 2.58 (IQR: 1.4-3.9). The in-hospital death rate was 23% for men and 29% for women. The delta lactate was significantly higher in women (P=0.0070), driven by a lower initial lactate (P=0.0277). In a multivariate regression model controlled for age and gender, a statistically significant correlation was noted between an increase in the delta lactate and in-hospital death (P=0.0323; R(2)=11.3%). The results of this single-center study suggest that an increase in serum lactic acid is significantly associated with higher in-hospital death.